Nonlinear analysis of reinforced concrete structures using a new constitutive model - Khalfallah, Salah; Charif, Abdelhamid; Naimi, Mohammed (European Journal of Computational Mechanics, 2004)
An analytical model, which can simulate the biaxial description of the nonlinear behavior of reinforced concrete structures, is introduced. The behavior of concrete is assumed orthotropic inside the ultimate failure surface and a compressive softening law of concrete is presented. The behavior of cracked concrete is simulated using the smeared crack model, which the tension stiffening effect based on a cracking criterion derived from the fracture mechanics principles is considered. A computer program is developed for analyzing the over and under-reinforced concrete beams. Several parameters such as the non-linearity proprieties, the cut off and tension stiffening models and shear retention factor are studied. The correlation between analytical and experimental results shows the validity of the proposed models and the significance of various effects. The global responses are evaluated to verify simultaneously the reliability of the proposed model and the performance of the numerical program.